Extreme dust storm over the eastern Mediterranean in September 2015: Satellite, lidar, and surface observations in the Cyprus region - Mamouri, Rodanthi-Elisavet; Ansmann, Albert; Nisantzi, Argyro; Solomos, Stavros; Kallos, George B.; Hadjimitsis, Diofantos G. (My University, 2016)
A record-breaking dust storm originating from desert regions in northern Syria and Iraq occurred over the eastern Mediterranean in September 2015. In this contribution of a series of two articles (part 1, observations; part 2, atmospheric modeling), we provide a comprehensive overview of the aerosol conditions during this extreme dust outbreak in the Cyprus region. These observations are based on satellite observations (MODIS, moderate resolution imaging spectroradiometer) of aerosol optical thickness (AOT) and Ångström exponent, surface particle mass (PM10) concentrations measured at four sites in Cyprus, visibility observations at three airports in southern Cyprus and corresponding conversion products (particle extinction coefficient, dust mass concentrations), EARLINET (European Aerosol Research Lidar Network) lidar observations of dust vertical layering over Limassol, particle optical properties (backscatter, extinction, lidar ratio, linear depolarization ratio), and derived profiles of dust mass concentrations. Maximum 550 nm AOT exceeded values of 5.0, according to MODIS, and the mass loads were correspondingly > 10gm-2 over Larnaca and Limassol during the passage of an extremely dense dust front on 8 September 2015. Hourly mean PM10 values were close to 8000μgm-3 and the observed meteorological optical range (visibility) was reduced to 300-750m at Larnaca and Limassol. The visibility observations suggest peak values of the near-surface total suspended particle (TSP) extinction coefficients of 6000Mm-1 and thus TSP mass concentrations of 10000μgm-3. The Raman polarization lidar observations mainly indicated a double layer structure of the dust plumes (reaching to about 4km height), pointing to at least two different dust source regions. Dust particle extinction coefficients (532nm) already exceeded 1000Mm-1 and the mass concentrations reached 2000μgm-3 in the elevated dust layers on 7 September, more than 12h before the peak dust front on 8 September reached the Limassol lidar station around local noon. Typical Middle Eastern dust lidar ratios around 40sr were observed in the dense dust plumes. The particle depolarization ratio decreased from around 0.3 in the lofted dense dust layers to 0.2 at the end of the dust period (11 September), indicating an increasing impact of anthropogenic haze.
Keywords: Saharan dust; Polarization lidar; Mineral dust; Mass concentration; Aerosol products; Raman lidar; Earlinet